The Range of Applying the Foreign Law in the Jordanian Judiciary Against the Civil Proceedings Caused Due to a Crime - AL-KHASILAT, Abdullah Ahmed; NASRIDEEN, Tamara Yaqoub (Journal of Advanced Research in Law and Economics, 2020)
The research aims to clarify the legal solution about an important issue, which is to identify which legal rule needs to be applied to a civil lawsuit that has been raised based on a public right lawsuit in the criminal court, it was noticed that there is a Jurisprudential and Judicial Dispute while dealing with this subject, therefore the research addressed the differences in opinions and the Jordanian legislator's point of view about this matter. At the end of the research, a conclusion for the need for a clear and explicit provision statement to melt this dispute.